Knowledge and preventive practices regarding breast cancer among nursing students in Northern Mexico: A cross-sectional correlational study - Cervera Baas, Maria Eugenia; Barajas Sánchez, Julio; Gutierrez Torres, Karina; Feliciano Domínguez , Efren (Palembang MediRose Publisher, 2025)
Background: Breast cancer is one of the most prevalent non-communicable diseases and a leading cause of morbidity and mortality among women worldwide. It is characterized by the uncontrolled proliferation of malignant breast cells, leading to tumor growth and potential metastasis to distant organs. Early detection and preventive behaviors, such as breast self-examination (BSE), are critical in reducing disease burden. Objective: This study aimed to examine the relationship between breast cancer knowledge and preventive practices among nursing students in northern Mexico. Methods: A cross-sectional, correlational study was conducted from January to February 2024, involving 118 Bachelor of Nursing students aged 18 years or older. Participants were selected through simple random sampling. Data were collected using a structured, self-administered questionnaire assessing sociodemographic characteristics, attitudes toward BSE, and knowledge of breast cancer. The instrument demonstrated acceptable internal consistency (Cronbach’s ? = 0.632). Data were analyzed using SPSS version 23, with descriptive statistics summarizing participant characteristics and Spearman’s rank-order correlation assessing the association between knowledge and preventive measures. Statistical significance was set at p < 0.05. Results: The majority of participants were female (82%), with a mean age of 21.9 years. Most respondents demonstrated awareness of breast cancer and early detection methods; however, regular BSE practice was reported by only 33%. A moderate, statistically significant correlation was observed between knowledge and preventive measures (rs = 0.57, p = 0.001). Conclusion: Findings highlight the need for targeted educational interventions in nursing curricula to strengthen knowledge and reinforce preventive practices, ultimately enhancing early detection and improving patient outcomes.